2021
DOI: 10.1136/bmjopen-2021-050881
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability, utilisation and cost in the provision of critical care in Tanzania: a protocol for a systematic review

Abstract: IntroductionCritical care is essential in saving lives of those that are critically ill, however, provision of critical care can be costly and heterogeneous across lower-resource settings. This paper describes the protocol for a systematic review of the literature that aims to identify the reported costs and resources available for the provision of critical care and the forms of critical care provision in Tanzania.Methods and analysisThe review will follow the Preferred Reporting Items for Systematic Reviews a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
0
15
0
Order By: Relevance
“… 20 The full methodological protocol used in this review is available elsewhere. 20 For this study, critical care is defined as the identification, monitoring and treatment of patients with critical illness through the initial and sustained support of vital organ functions. 7 It involves enhanced monitoring, treatment and attention required by a patient as a result of the life-threatening aspects of an illness or injury.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“… 20 The full methodological protocol used in this review is available elsewhere. 20 For this study, critical care is defined as the identification, monitoring and treatment of patients with critical illness through the initial and sustained support of vital organ functions. 7 It involves enhanced monitoring, treatment and attention required by a patient as a result of the life-threatening aspects of an illness or injury.…”
Section: Methodsmentioning
confidence: 99%
“…A study was considered eligible if it was published in English and reported on the provision of critical care, 20 services offered under critical care, resources and/or costs incurred by the health system or health providers in providing critical care in Tanzania. A detailed inclusion/exclusion criterion can be found in online supplemental 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations